2021
DOI: 10.1080/15374416.2021.1881904
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations between Callous-unemotional (CU) Traits and School-based Affiliative Relationships among South Korean Children

Abstract: Objective: Callous-unemotional traits (CU) traits are characterized by low empathy, guilt, and reduced sensitivity to others' feelings, along with a reduced drive for social affiliation. However, little is known about the relationships between CU traits and social affiliation in the school context, or the influence of gender on these associations. This study tested reciprocal associations between CU traits and school-based affiliative relationships and explored gender as a potential moderator. Method: The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
(88 reference statements)
0
4
0
3
Order By: Relevance
“…Previous studies on CU traits and peer rejection presented mixed results. Some research demonstrated a significant association between the two variables [ 7 , 62 ], and some others did not find an association [ 20 , 63 ]. This may be due to subjective differences between different informants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on CU traits and peer rejection presented mixed results. Some research demonstrated a significant association between the two variables [ 7 , 62 ], and some others did not find an association [ 20 , 63 ]. This may be due to subjective differences between different informants.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to subjective differences between different informants. For example, research that used peer reports had inconsistent results with research that used children’s self-reports [ 62 , 63 ]. This study used a teacher-reported approach, yet social interactions between children often occur outside of the adult’s view [ 64 ], and thus may have some influence on the result of this study.…”
Section: Discussionmentioning
confidence: 99%
“…De los estudios encontrados, Conradi, et al (2016) fue el único en tener una muestra de más de 1,000 sujetos. Por otro lado, Bobbio y Arbach (2019), Hwang, et al (2021), Paula Vagos, et al (2022), presentan muestras de menos de 280 participantes y el resto de las investigaciones como las de Pasalich, et al, (2012), Celedón, et al (2016, Clark y Frick (2018), Kimonis, et al (2019, Mooney, et al (2019), Acosta, et al (2020) contaban con muestras iguales o menores de 100 participantes.…”
Section: Discussionunclassified
“…De igual manera, solamente dos de dichos estudios (Suhlim Hwang et al 2021.;Vagos et al 2022) contaron con un diseño longitudinal. Lo anterior da cuenta de que la mayoría de los estudios no cuenta con una muestra grande representativa que genere mayores datos estadísticos para una mayor validez y confiabilidad en los hallazgos y resultados presentados.…”
Section: Discussionunclassified
“…CU traits are associated with greater conflict and less closeness between teachers and students (Baroncelli & Ciucci, 2020 ), impaired peer relationships (Wagner et al, 2020 ), and academic underachievement (Horan et al, 2016 ). This has led to recent calls to recognize the potential utility of CU traits for addressing disruptive behavior in school, with teacher-child interaction identified as a potential target for intervention (Hwang et al, 2022 ; Willoughby et al, 2022 ).…”
mentioning
confidence: 99%